2023
DOI: 10.3390/healthcare11142001
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Foam Roller and Stretching to the Lead Hip on Golfers Swing: A Randomized Crossover Trial

Abstract: Golfers with decreased range of motion (ROM) of their leading hip internal rotation (IR) have increased lumbar rotation ROM and load. This study investigated the effects of foam roller (FR) applied to their leading hip muscles combined with stretching to the leading hip together with lumbar rotation ROM during the golf swing. The study design was a crossover design. Subjects were allocated to one of two groups comprising FR and dynamic stretching (FR + DS) or practice swing. Motion analysis was used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, in some cases, the combination of SMR with static stretching has superior effects in increasing the ROM compared to one of these exercises performed in isolation [ 72 , 76 ]. Reinforcing this idea, other studies stated that the use of dynamic stretching or DS + FR [ 54 , 56 , 74 , 96 ], as well as aerobic running/combined aerobic running + SMR [ 70 ], improve sit-and-reach performance, knee flexibility, and hip ROM results to a greater degree compared to isolated FR/SMR, especially in the short term (<10 min). However, Warneke et al [ 97 ] reported that any immediate enhancements in range of motion (ROM) could not be solely ascribed to foam rolling, conjecturing that warm-up effects might be accountable independently of the FR or replicating the rolling motion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some cases, the combination of SMR with static stretching has superior effects in increasing the ROM compared to one of these exercises performed in isolation [ 72 , 76 ]. Reinforcing this idea, other studies stated that the use of dynamic stretching or DS + FR [ 54 , 56 , 74 , 96 ], as well as aerobic running/combined aerobic running + SMR [ 70 ], improve sit-and-reach performance, knee flexibility, and hip ROM results to a greater degree compared to isolated FR/SMR, especially in the short term (<10 min). However, Warneke et al [ 97 ] reported that any immediate enhancements in range of motion (ROM) could not be solely ascribed to foam rolling, conjecturing that warm-up effects might be accountable independently of the FR or replicating the rolling motion.…”
Section: Discussionmentioning
confidence: 99%